Pure progressive aphemia. Issue 8 (August 1993) - Cohen, L; Benoit, N; Van Eeckhout, P; Ducarne, B; Brunet, P
Abstract : Aphemia, also called anarthria or severe apraxia of speech, is a rare disorder of speech production usually resulting from vascular lesions affecting the inferior premotor cortex of the left hemisphere. A patient presenting with aphemia as the sole manifestation of primary progressive aphasia (PPA) is reported.